Clinical Programs That Allow Both Compensation and Credit: A Model Program for Law Schools - Roy D. Simon Jr.; Tom Leahy (Washington University Law Quarterly, 1984)
In this Article, the authors set out the arguments for and against "credit-plus-pay" clinical programs, categorizing the arguments on both sides as either educational arguments or economic arguments. The authors then develop a model credit-plus-pay program. The authors begin with two fundamental premises. First, every law school should be free to design a curriculum that is best suited to serve its own students and produce competent lawyers. Second, each program offered by a law school should be evaluated on its own educational merits, not on the basis of a rigid litmus test such as compensation.
Keywords: Legal education; United States